2023
DOI: 10.3390/s23229161
|View full text |Cite
|
Sign up to set email alerts
|

Crack Segmentation Extraction and Parameter Calculation of Asphalt Pavement Based on Image Processing

Zhongbo Li,
Chao Yin,
Xixuan Zhang

Abstract: Crack disease is one of the most serious and common diseases in road detection. Traditional manual methods for measuring crack detection can no longer meet the needs of road crack detection. In previous work, the authors proposed a crack detection method for asphalt pavements based on an improved YOLOv5s model, which is a better model for detecting various types of cracks in asphalt pavements. However, most of the current research on automatic pavement crack detection is still focused on crack identification a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…c is the parameter controlling the rate of decay, determined by 𝛿, 𝑐 = −16log[0.1(𝛿 − 1)] π 2 ⁄ . The voting field intensity S of point O at any given point P is determined by (5).…”
Section: Geometric Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…c is the parameter controlling the rate of decay, determined by 𝛿, 𝑐 = −16log[0.1(𝛿 − 1)] π 2 ⁄ . The voting field intensity S of point O at any given point P is determined by (5).…”
Section: Geometric Representationmentioning
confidence: 99%
“…Many studies focus on enhancing the classical Otsu threshold method, K-means clustering, and other algorithms to determine the optimal gray value segmentation threshold. Li et al [5] employed histogram equalization and linear gray value transformation to accentuate crack features, eliminate noise, and applied the Zhang-Suen refinement algorithm and connectivity domain threshold method for crack skeleton extraction and skeleton burrs removal. Vivekananthan et al [6] utilized the Sobel filter for crack edge detection, combining max-min gray level discrimination with the Otsu method for improved segmentation accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, DL models often consume large computational resources, resulting in slower processing times for classification systems. To address that issue, classical image processing algorithms with lower computations have been employed for mango segmentation, such as the approach of utilizing a fixed threshold to segment objects from grayscale images, as described in the study in [14]. However, that method lacks adaptability when the color of the mangoes has changed.…”
Section: Mango Segmentationmentioning
confidence: 99%
“…standard deviation of one, thereby eliminating differences arising from varying scales among the features. The equation for Standard Scaler is shown as follows (14).…”
Section: Data Preprocessingmentioning
confidence: 99%
“…Test results showed that the average detection error of the model was only 6.521 pixels, demonstrating its precision in pavement defect localization. However, although two-stage target detection models exhibit higher accuracy in pavement distress detection tasks, the direct application in engineering detection tasks is limited due to their large model parameters, high computational complexity, and slower recognition speed compared to one-stage detection models 22 .…”
Section: Introductionmentioning
confidence: 99%